Sufism Irfani and Its Implications for Islamic Religious Education in Indonesia - Mohammad Ahyan Yusuf Sya'bani (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
This paper aims to know the levels and methods of sufism Irfani and reveal the implications of sufism Irfani on Islamic Religious Education. The primary data sources are sources directly related to the main focus of this research related to sufism Irfani implications in learning as well as all books on Islamic religious education. Secondary sources are all documents, archives, magazines, and reports of research results as well as manuscripts and writings related to the concept of Sufism Irfani implications in learning Islamic religious education. The research method used is a qualitative research method by choosing the type of literature research to review literature descriptively so that the event is revealed as it is. The purpose of this study is so that the results can be described objectively with the actual situation. Qualitative research perspective, the approach used for this research is a grounded theory approach that functions to find theories (combined theoretical explanations) so that it can be analyzed by sufism Irfani and its implications in the context of Islamic Religious Education in Indonesia. Meanwhile, the results show that the contextualization and implications of Sufism in Islamic Religious Education can be seen from the analysis of elements of Islamic religious education such as students, teachers, learning objectives, curriculum, learning strategies and methods, teaching materials, facilities, and infrastructure, all of which are directed at internalizing the values of goodness and Islamic teachings where it is also interpreted as an effort to internalize the side of esotericism and the inner state inÂ  Sufism Irfani's perspective on all subjects of education, both teachers and students.